Is agricultural insurance fulfilling its promise for the developing world? - Kramer, Berber; Hazell, Peter B. R.; Alderman, Harold; Ceballos, Francisco; Kumar, Neha; Timu, Anne G. (International Food Policy Research Institute, 2021)
Agricultural insurance has attracted considerable interest in recent years. Innovations in agricultural index insurance have raised expectations that the private sector can overcome shortcomings associated with more traditional indemnity-based products like multi-peril crop insurance, and contribute to strengthen agricultural risk management at scale across developing countries. This paper updates previous reviews on agricultural insurance but differs in that it goes beyond the prognosis that recent innovations can help make insurance more commercially viable. As such, it addresses two important challenges that have received limited attention. First, it distinguishes different types of farm households and recognizes that many are excluded from the insurance market, describing additional innovations that can help make insurance more accessible to these excluded groups. Second, it acknowledges that insurance for catastrophic risks is unaffordable for most farmers and summarizes new developments in disaster assistance and safety net programs that can provide broader protection against these risks.